Mineralogical Analysis of Primary and Secondary Source Sediments to Linnévatnet, Spitsbergen, Svalbard, 2006 - Lauren Marie Perreault (Arctic Data Center, 2013)
Linnévatnet, Spitsbergen, Svalbard is a high Arctic lake containing a sediment record that extends through most of the Holocene. Laminated lake sediments such as those found in Linnévatnet can serve as high resolution proxies for long term climate change. This study utilizes detailed mineralogical analysis to identify changes in the source of sediments to Linnévatnet during the late Holocene. These climatically sensitive sediment sources include a major proglacial river; alluvial fans, solifluction lobes and the meltwater stream from a small cirque are secondary sources. Distinct bedrock lithologies (phyllite, sandstone, carbonate and dolerite) in the valley strike north-south parallel to the lake, making provenance work possible. Pebble counts, conducted in the field at each sediment source, reveal a strong correlation between cobble and boulder lithology and underlying bedrock source. Laboratory identification of the gravel fraction of surficial sediment samples indicates increased break down of phyllite and carbonate in comparison to the sandstone. Grain size analysis of source sediments implicates differences in the mechanism of sediment transport and deposition at different sources. Unique mineral compositions were identified for each sediment source studied using paired x-ray diffractometer (XRD) and quantitative analysis of the sand, silt and clay sized fractions. West shore solifluction sources are recognized by the abundance and presence of sheet silicates (muscovite, chlorite, kaolinite) in all size fractions. The cirque outwash stream is distinguished by higher amounts of chlorite in all size fractions and the abundance of albite in the silt fraction. East shore sources are characterized by higher amounts of carbonate minerals and the presence of accessory minerals (rutile, pyroxene). Linnéelva sediments contain relatively less carbonate, albite and chlorite/kaolinite than the west and east shore sources. Continuous grain size analysis of four surface cores from different locations in the lake show variations in grain size through time, indicating changes in sediment transport. Paired XRD and quantitative analysis of the silt and clay fractions from core subsamples indicate changes in mineralogical composition down core at all locations but are limited in scope. Higher amounts of silt, paired with an increase in chlorite/kaolinite and a distinct stratigraphy, indicate increased glacier activity in the core proximal to the cirque. Higher amounts of sand, decoupled from silt trends and paired with the presence of local mineralogy (orthopyroxene, calcite) in the two deep basin cores indicate increased east slope activity. Differences in grain size distribution of the two deep basin cores implicate solifluction lobes as a contributor to sedimentation in the north end of the deep basin.